Understanding the relationship between social influence and soccer fans' satisfaction in Singapore - Lo, Wei Cong (2019)
Social influence in the environment of which one is exposed to has been one of the major motivators for spectatorship in sport. The social influence in soccer is present in soccer fans' daily living and it has an effect on their attitude, emotion, and behaviour towards spectating. The purpose of the study is to understand the relationship between social influence in spectating and satisfaction in soccer fans. It aims to identify the social influencing motivators in an individual's social environment and establish a relationship between their satisfaction in spectating soccer. An interview session was conducted to 8 potential male soccer fans (age; 21 – 29) at respective stadiums. Convenience sampling method was adopted to identify the participants before the start of the Singapore Premier League. Social influencing motivators gathered from the participants’ response are categorised into themes. Qualitative analysis from the result shows that there are 3 main social influencing factors; namely Personal Background and Experience, Companionship, and External Environmental Factors can escalate fan’s satisfaction that leads to repeated spectating behaviour. The theoretical foundations in this study are based on the theory of planned behaviour, symbolic interactionism and expectation confirmation theory. Despite the match results, the subjects have identified themselves as satisfied loyal soccer fans and soccer is important in their life with a mean score of 8 out of 10. The model of social influence and satisfaction was developed accordingly with the implementation of the theories and identified themes that lead to a revisit motivation to spectate the soccer matches.